The Effects of Purple Sweet Potato (Ipomoea Batatas L.) Ethanol Extract on Bladder Urothelial Layer and Smooth Muscle Thicknesses in Menopausal Female Wistar Rats - Putra, Bismantara Aditya; Santosa, Kadek Budi; Niryana, I Wayan; Golden, Nyoman; Duarsa, Gede Wirya Kusuma; Suryawisesa, Ida Bagus Made (Folia Medica Indonesiana, 2023)
Highlights: Purple sweet potatoes cultivated in Bali, Indonesia, were found to be rich in phytoestrogen due to the high levels of anthocyanin-type flavonoids. The phytoestrogen in purple sweet potato ethanol extract demonstrated estrogenic activity and the potential to substitute hormone replacement therapy (HRT) as the treatment of lower urinary tract symptoms. Abstract Postmenopausal women experience estrogen hormone deficiency, which can cause thinning of the smooth muscle and urothelial layer of the bladder, leading to lower urinary tract symptoms (LUTS). Hormone replacement therapy (HRT) has been the primary choice for addressing these problems. However, long-term prescription of HRT can result in several adverse effects, including a higher risk of breast cancer and cardiovascular diseases. Phytoestrogen, an estrogen-like compound derived from plants such as purple sweet potatoes (Ipomoea batatas L.), contains anthocyanin that could serve as a better alternative to estrogen replacement therapy. This study aimed to demonstrate the effects of phytoestrogens in purple sweet potatoes on the histomorphology of the bladder in menopausal female Wistar rats (Rattus norvegicus). This experimental study used a posttest-only control group design. A total of 36 Wistar rats undergoing ovariectomy were randomly assigned into two groups, with 18 samples in each group. The experimental group received the purple sweet potato ethanol extract orally, while the control group received a placebo. The structures of the smooth muscle and urothelial layer of the bladder were observed using a microscope. Data were analyzed using an independent t-test to compare bladder smooth muscle and urothelial layer thickness between groups, with a significance of p<0.05. A normality test was performed to determine the normal distribution of the data. Normally distributed data were assessed to find the mean and standard deviation (SD). Significant differences were found in the mean thickness of the smooth muscle and urothelial layer between both groups (p=0.00), with both being thicker in the experimental group. In conclusion, phytoestrogens in purple sweet potatoes can influence the histomorphology of the bladder. Ovariectomized female Wistar rats that received purple sweet potato ethanol extract exhibited thicker smooth muscle and urothelial layer of the bladder.